Generierung von AUTOSAR-Modellen aus UML-Spezifikationen - Meyer, Jan; Holtmann, Jörg; Koch, Thorsten; Meyer, Matthias (10. Paderborner Workshop Entwurf mechatronischer Systeme)
Die Komplexität moderner Fahrzeuge steigt aufgrund der zunehmenden Anzahl von Funktionen, die durch elektronische Systeme umgesetzt werden. Insbesondere nehmen die Abhängigkeiten zwischen den an der Entwicklung beteiligten Fachdisziplinen und der Softwareanteil massiv zu. Wir haben einen für die Automobilindustrie angepassten, zum Reifegradmodell Automotive SPICE konformen Prozess für die Entwicklung von Steuergeräten konzipiert, der ein fachdisziplinübergreifendes Systems Engineering und einen systematischen Übergang in die Softwareentwicklung unterstützt. Im Kontext dieses Entwicklungsprozess beschreiben wir in diesem Beitrag den Übergang vom UML-basierten Softwareentwurf zum in der Automobilindustrie etablierten AUTOSAR-Standard mit Hilfe einer automatischen Modelltransformation. So werden fehleranfällige und zeitaufwändige manuelle Tätigkeiten reduziert. Wir haben die Generierung von AUTOSAR-Modellen gemeinsam mit dem international tätigen Automobilzulieferer Hella KGaA Hueck & Co. in seriennahen Entwicklungsprojekten praktisch erprobt und Zeit- und Kostenersparnisse festgestellt.

IccTA: Detecting Inter-Component Privacy Leaks in Android Apps - Li, Li; Bartel, Alexandre; Bissyande, Tegawende F.; Klein, Jacques; Le Traon, Yves; Arzt, Steven; Rasthofer, Siegfried; Bodden, Eric; Octeau, Damien; McDaniel, Patrick (2015 International Conference on Software Engineering (ICSE))
Keywords: CROSSING; ATTRACT; ITSECWEBSITE

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

SeSAME: Modeling and Analyzing High-Quality Service Compositions - Arifulina, Svetlana; Becker, Matthias; Platenius, Marie Christin; Walther, Sven (Proceedings of the 29th IEEE/ACM International Conference on Automated Software Engineering (ASE 2014))
Today, software components are traded on markets in form of services. These services can also be service compositions consisting of several services. If a software architect wants to provide such a service composition in the market for trade, she needs to perform several tasks: she needs to model the composition, to discover existing services to be part of that composition, and to analyze the composition's functional correctness as well as its quality, e.g., performance. Up to now, the architect needed to find and use different tools for these tasks. Typically, these tools are not interoperable with each other. We provide the tool SeSAME that supports a software architect in all of these tasks. SeSAME is an integrated Eclipse-based tool-suite providing a comprehensive service specification language to model service compositions and existing services. Furthermore, it includes modules for service matching, functional analysis, and non-functional analysis. SeSAME is the first tool that integrates all these tasks into one tool-suite and, thereby, provides holistic support for trading software services. Thus, it contributes to a software provider's market success.

Security and Privacy Challenges in On-The-Fly Computing - Petrlic, Ronald; Jungmann, Alexander; Platenius, Marie Christin; Schäfer, Wilhelm; Sorge, Christoph (Tagungsband der 4. Konferenz Software-Technologien und -Prozesse (STeP 2014))
On-The-Fly (OTF) Computing constitutes an approach towards highly dynamic and individualized software markets. Based on service-oriented computing, OTF Computing is about realizing global markets of services that can be flexibly combined. We report on our current research activities, the security and privacy implications thereof, and our approaches to tackle the challenges. Furthermore, we discuss how the security and privacy challenges are addressed in research projects similar to OTF Computing.

ScenarioTools Real-Time Play-Out for Test Sequence Validation in an Automotive Case Study - Brenner, Christian; Greenyer, Joel; Holtmann, Jörg; Liebel, Grischa; Stieglbauer, Gerald; Tichy, Matthias (Proceedings of the 13th International Workshop on Graph Transformation and Visual Modeling Techniques (GT-VMT 2014))
In many areas, such as automotive, healthcare, or production, we find software-intensive systems with complex real-time requirements. To efficiently ensure the quality of these systems, engineers require automated tools for the validation of the requirements throughout the development. This, however, requires that the requirements are specified in an analyzable way. We propose modeling the specification using Modal Sequence Diagrams (MSDs), which express what a system may, must, or must not do in certain situations. MSDs can be executed via the play-out algorithm to investigate the behavior emerging from the interplay of multiple scenarios; we can also test if traces of the final product satisfy all scenarios. In this paper, we present the first tool supporting the play-out of MSDs with real-time constraints. As a case study, we modeled the requirements on gear shifts in an upcoming standard on vehicle testing and use our tool to validate externally generated gear shift sequences.

Generating Modelica Models from Software Specifications for the Simulation of Cyber-physical Systems - Pohlmann, Uwe; Holtmann, Jörg; Meyer, Matthias; Gerking, Christopher (Proceedings of the 40th Euromicro Conference on Software Engineering and Advanced Applications (SEAA))

The MechatronicUML Method: Model-Driven Software Engineering of Self-Adaptive Mechatronic Systems - Becker, Steffen; Dziwok, Stefan; Gerking, Christopher; Heinzemann, Christian; Schäfer, Wilhelm; Meyer, Matthias; Pohlmann, Uwe (Proceedings of the 36th International Conference on Software Engineering (Posters))

A Modelica Coordination Pattern Library for Cyber-Physical Systems - Pohlmann, Uwe; Dziwok, Stefan; Meyer, Matthias; Tichy, Matthias; Thiele, Sebastian (Proceedings of the 7th International ICST Conference on Simulation Tools and Techniques)

The MechatronicUML Design Method - Process and Language for Platform-Independent Modeling - Becker, Steffen; Dziwok, Stefan; Gerking, Christopher; Schäfer, Wilhelm; Heinzemann, Christian; Thiele, Sebastian; Meyer, Matthias; Priesterjahn, Claudia; Pohlmann, Uwe; Tichy, Matthias